2017
DOI: 10.1002/ece3.2912
|View full text |Cite
|
Sign up to set email alerts
|

Improving inference for aerial surveys of bears: The importance of assumptions and the cost of unnecessary complexity

Abstract: Obtaining useful estimates of wildlife abundance or density requires thoughtful attention to potential sources of bias and precision, and it is widely understood that addressing incomplete detection is critical to appropriate inference. When the underlying assumptions of sampling approaches are violated, both increased bias and reduced precision of the population estimator may result. Bear (Ursus spp.) populations can be difficult to sample and are often monitored using mark‐recapture distance sampling (MRDS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 55 publications
3
62
0
Order By: Relevance
“…We note the Becker and Quang (2009) population estimate of 618.4 brown bears (26.3 brown bears/1,000 km 2 ) is much lower than the MRDS_2PN model estimate of 746.1 (Table 2) due mainly to un-modeled heterogeneity in the full independence model used by Becker and Quang (2009). Schmidt et al (2017) are not justified in dropping the MR data since 2 of their reported MR probabilities were calculated using a full independence MRDS model (Becker & Quang, 2009) and, as a result, are biased high due to un-modeled heterogeneity.…”
Section: Is Mark-rec Ap Ture Data Needed?mentioning
confidence: 63%
See 4 more Smart Citations
“…We note the Becker and Quang (2009) population estimate of 618.4 brown bears (26.3 brown bears/1,000 km 2 ) is much lower than the MRDS_2PN model estimate of 746.1 (Table 2) due mainly to un-modeled heterogeneity in the full independence model used by Becker and Quang (2009). Schmidt et al (2017) are not justified in dropping the MR data since 2 of their reported MR probabilities were calculated using a full independence MRDS model (Becker & Quang, 2009) and, as a result, are biased high due to un-modeled heterogeneity.…”
Section: Is Mark-rec Ap Ture Data Needed?mentioning
confidence: 63%
“…Laake and Borchers (2004) state that population estimates from MRDS models "obtained under the assumption of full independence will tend to be negatively biased compared to estimates obtained under the assumption of point independence." Schmidt et al (2017) justify dropping the MR model with the statement: "marginal detection probabilities at the apex of the detection function are quite high for both the pilot and observer (Becker & Christ, 2015;Becker & Quang, 2009;Walsh et al, 2010) suggesting that the joint p d may approach 1.0 in many cases." Schmidt et al (2017) justify dropping the MR model with the statement: "marginal detection probabilities at the apex of the detection function are quite high for both the pilot and observer (Becker & Christ, 2015;Becker & Quang, 2009;Walsh et al, 2010) suggesting that the joint p d may approach 1.0 in many cases."…”
Section: Is Mark-rec Ap Ture Data Needed?mentioning
confidence: 99%
See 3 more Smart Citations